Comparison of the Flash Profile and the Napping ®-UFP Techniques in the sensory characterization of hot-dog - Puma-Isuiza, Gustavo Gavino (2020)
The similarity between the Flash Profile and the Napping®-Ultra Flash Profile (Napping®-UFP) techniques was evaluated using the vector correlation coefficient (Rv). For this purpose, two commercial hot-dog brands from the Lima market and two formulations obtained by Kansei Engineering were sensory characterized. In the Flash Profile, consumers generated and rated their own descriptors, which were processed using the generalized Procrustes analysis. In Napping®-UFP, consumers positioned and described the hot-dog samples on an A3 size sheet. The coordinates (x, y) of each sample and the descriptive terms were processed by multiple factor analysis. The consensus index (Rc = 61.2 %) and the overlap of the confidence ellipses in samples HD2.1 and HD2.2 showed that they did not have a significant sensory difference (p-value < 0.05). Finally, the Rv value (0.93) determined a high similarity between both sensory techniques.